1994
DOI: 10.1080/10426509408034274
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Synthesis and Theoretical Calculations of the Elusive Polycyclic Arene Episulfides

Abstract: In pursuit of the thus far illusive polycyclic arene episulfides (PAE)as model compounds for further study in relation to chemistry-based cancer researchwe have attempted the synthesis of phenanthrene episulfide by using phenanthrene oxide, phenanthrene, and 5,7-dihydrodibenzo[c,e]thiepin as key starting materials. Following preliminaty theoretical calculations of the targeted PAE's, the synthesis of 9,10-episulfide-trans-7,8-dihydroxy-7,8-dihydro[a]pyre.ne has been initiated. Our results indicate that apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, the thermodynamic [7] and kinetic [8] instability of the aromatic episulfides has complicated the synthesis of such compounds [9], and only a few have been isolated [10]. An attempted experimental work together with theoretical calculations oriented to direct the efforts for synthesizing polycyclic arene episulfides to make them available for cancer-related research has been reported lately [11a].…”
mentioning
confidence: 99%
“…However, the thermodynamic [7] and kinetic [8] instability of the aromatic episulfides has complicated the synthesis of such compounds [9], and only a few have been isolated [10]. An attempted experimental work together with theoretical calculations oriented to direct the efforts for synthesizing polycyclic arene episulfides to make them available for cancer-related research has been reported lately [11a].…”
mentioning
confidence: 99%
“…Polycyclic arene episulfides (thiiranes) are highly unstable both thermodynamically 74 and kinetically, 75 and consequently, only few polycyclic aromatic episulfides have been synthezised so far. They undergo easy thermal desulfurization because the driving force toward aromatization, therefore, their thermodynamic stability increases the higher is the aromatic character of the ring system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Polycyclic aromatic episulfides, the sulfur analogues of PAH epoxides, maintain the basic requirements of PAH carcinogenicity [41], although the thermodynamic [76] and kinetic [77] instability of the aromatic episulfides has complicated the synthesis of such compounds. However, the synthesis as well as studies on the cytotoxicity and mutagenicity of some aromatic diol episulfides have been recently accomplished [78][79][80].…”
Section: Carbocations From Miscellaneous Het-ero-pahsmentioning
confidence: 99%